2022
DOI: 10.56303/jhnresearch.v1i3.21
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Economic Status, Infectious Diseases and Urinary Iodine Excretion with Stunting Incidence of Elementary School Children in IDD Endemic Areas, Enrekang Regency

Abstract: This study aimed to determine the relationship of economic status, infectious diseases, and Urinary Iodine Excretion (UIE) with the incidence of stunting in elementary school children in IDD endemic areas, Enrekang Regency. This research was an observational analytic study with a cross-sectional approach. Subjects in this study were taken by purposive sampling as many as 100 children aged 6-12 years. Research data were collected using a questionnaire, microtoise, and UIE Lab Test and then processed using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…This becomes a transformation of the growth and development of bacteria and viruses that can cause health problems. The same study in the Enrekang village found a significant relationship between infectious diseases and stunting (30). Even though the child lives, grows, and develops in his own home, if it is not based on healthy and clean housing conditions (hygiene sanitation), then there is a vulnerability to nutritional problems.…”
Section: Relationship Between Residence Status and Stunting Incidentsmentioning
confidence: 94%
“…This becomes a transformation of the growth and development of bacteria and viruses that can cause health problems. The same study in the Enrekang village found a significant relationship between infectious diseases and stunting (30). Even though the child lives, grows, and develops in his own home, if it is not based on healthy and clean housing conditions (hygiene sanitation), then there is a vulnerability to nutritional problems.…”
Section: Relationship Between Residence Status and Stunting Incidentsmentioning
confidence: 94%
“…The attitude is assessed based on the tendency to behave positively or negatively concerning balanced nutrition. The cut-off is good: if the score is ≥ 76-100% (24-32), enough: if the score is 51-75% (16)(17)(18)(19)(20)(21)(22)(23), and less: if the score is 25-50% (8)(9)(10)(11)(12)(13)(14)(15). Behaviour is a set of behaviours related to balanced nutrition that is practised based on awareness as a result of learning.…”
Section: Methodsmentioning
confidence: 99%
“…Various factors cause stunting in Indonesian children. Recent studies suggest that maternal height, exclusive breastfeeding, sanitation, clean and healthy living practices, diet, infectious diseases, and maternal knowledge have been proven as risk factors for stunting in toddlers and schoolchildren (20) (7) (17) (21). The latest study by in Enrekang Regency shows a significant relationship between knowledge and the incidence of stunting (22).…”
Section: Introductionmentioning
confidence: 99%